Pengembangan Kawasan Pariwisata Berbasis Kearifan Lokal Kampung Asey Besar: Studi Kasus : Kampung Asey Besar, Distrik Sentani Timur, Kabupaten Jayapura - Nichi Alter Mawene; Deasy Widyastomo; James Modouw (JURNAL WILAYAH, KOTA DAN LINGKUNGAN BERKELANJUTAN, 2024)
When viewed from a cultural perspective, the tourism industry indirectly plays an important role in the development of regional culture. Local wisdom is the potential of a culture that can be developed by the community so that the authenticity of that culture is maintained. It is hoped that the development of a tourism area based on local wisdom will have a positive impact on the people of Asey Besar Village. This research aims to determine the potential of a local wisdom-based tourism area in Asey Besar Village. To find out about the development of a tourism area based on local wisdom in Asey Besar Village, Jayapura Regency. The research method used is a qualitative descriptive method. Based on the research results, it was found that the potential for developing a tourism area based on local wisdom in Asey Besar Village is planned as a strategic area for traditional villages with known resources in the form of natural beauty, and has a landscape character with flora and fauna habitat, clear waters, topography, type of vegetation. Planning for regional development as a tourism area with local wisdom is carried out by increasing and developing investment in the social and cultural spatial structure of regional communities in Asey Besar Village. For the Government and Community, efforts must be made to preserve the potential of local wisdom in Asey Besar Village which supports tourism by the government and community as those responsible for protecting and maintaining local wisdom while maintaining culture as a characteristic of the tribal community of Asey Besar Village.